Dimensi "Nilai Bagi Pelanggan" (Customer Value Propositions-CVPs) Dalam Bisnis Ritel - Khusniyah Purwani (Jurnal Aplikasi Bisnis, 2017)
This paper surest a framework to identifiy competitive customer value proposition (CVPs) with four key dimensions of customer value in theJlrst step i.e. economic, functional, emotion and symbolic. A customer value proposition (CVPs) is developed on the basis of the these value dimensions, and evaluated for retailcompetitive advantage. Customer value and its CPVs have a key strategic role in organization to pursuit competitive advantage.